The need for assessing mental health literacy among teachers: an overview - Venkataraman, Surendran; Patil, Rajkumar; Balasundaram, Sivaprakash (International Journal of Research in Medical Sciences, 2019)
Background: The magnitude of mental disorders is a growing public health concern. According to World Health Organization (WHO) reports, one out of five children suffer from a disabling mental illness. Majority of mental illnesses start during the adolescent period. Management of mental illnesses start from recognizing the needy adolescent and providing appropriate therapy and support. Most of the children and adolescents are students who spend almost half of their active time in schools under observation of their teachers. Teachers interact with students daily and can spot the changes in their behavior before they develop full-blown symptoms. Hence, teachers can be a major resource of importance in providing basic mental health services. The teacher’s ability to identify the early signs of mental illness in adolescent students can be considered as the most critical and neglected area. Majority of the studies are conducted in the community or adolescent students and much less attention has been paid to the mental health literacy of educators, who are important role models and youth influencers in addressing mental health literacy. The scenario in India in this regard is highly disappointing with few studies done among teachers.